(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describle the clinical and laboratory profiles of patients with primary myelofibrosis (PMF) at the National Institute of Hematology and Blood Transfusion (NIHBT) between 2019 and 2024. Methods: A cross-sectional descriptive study was conducted on 181 PMF patients managed at the NIHBT from January 2019 to December 2024. Results: The cohort’s mean age was 62.7 ± 11.8 years, with a predominance of patients aged over 60. Constitutional symptoms were prevalent, including fatigue (89%), early satiety (70.2%), abdominal discomfort (70.2%), left upper quadrant pain (70.2%), and weight loss (63%). Physical examination revealed a high incidence of splenomegaly (95.6%) and anemia (89%). Laboratory findings indicated that 90.6% of patients presented with anemia (Hb≤120 g/L). Platelet counts were variable: 26.5% exhibited thrombocytosis (≥450 G/L), while 14.9% had thrombocytopenia (< 50 G/L). Leukocytosis (≥11 G/L) was observed in 51.4% of the cases. Bone marrow evaluation showed erythroid hypoplasia in 85.6% of patients; granulocytic lineage was increased in 42.5% and decreased in 17.1%, while 73.5% demonstrated megakaryocytic hyperplasia. Bone marrow fibrosis was classified as Grade II in 64.6% and Grade III in 35.4% of patients. The prevalence of the JAK2 mutation was 67.1%, whereas CALR and MPL mutations were identified in 3.9% and 1.1% of the cohort, respectively. Conclusion: Primary myelofibrosis patients present with heterogeneous clinical manifestations, characterized by high frequencies of splenomegaly and anemia. Laboratory analyses frequently reveal trilineage hematopoietic dysregulation in the bone marrow.